Invasive Fungal Infections in Children With Hematologic and Malignant Diseases. Issue 2 (March 2015) - Ozsevik, Sevinc N.; Sensoy, Gulnar; Karli, Arzu; Albayrak, Canan; Dagdemir, Ayhan; Belet, Nursen; Elli, Murat; Fisgin, Tunc; Ozyurek, Emel; Duru, Feride; Albayrak, Davut
Abstract : Background: To evaluate the clinical feature and outcome of invasive fungal infections (IFI) in children with hematologic and malign diseases. Patients and Methods: The medical records of children with hematologic and malignant diseases, who were hospitalized at our hospital between January 2010 and December 2011, were reviewed. Proven, probable, and possible IFIs were diagnosed according to the revised definitions of the European Organization for Research and Treatment of Cancer/Mycosis Study Group. The demographic, clinical, and laboratory characteristics of the patients who met the study criteria were evaluated. Results: IFI was diagnosed in 67 (7.2%) febrile episodes of 56 patients, of which 10 (1.2%) were proven, 20 (2%) probable, and 37 (4%) possible IFI. Blood culture of 10 cases with proven IFI yielded yeast and the most common isolated agent was Candida parapsilosis. Seventy percent of cases with fungemia had central venous catheter (CVC). Twenty cases with probable IFI had invasive mold infection. The cases with mold infection had higher median C-reactive protein values, lower neutrophil counts, and longer duration of neutropenia compared with the cases with yeast infection. A total of 14 patients (20.9%) died. Presence of CVC, bone marrow transplantation, total parenteral nutrition, prolonged fever, and proven/probable IFI were detected more often in patients who died, compared with patients who survived. Conclusions: IFIs are important causes of death in children with hematologic and malignant diseases. Mold infections are seen more frequently in cases with prolonged and profound neutropenia, and invasive yeast infections, especially with non- albicans Candida species, in cases with CVC. Early and effective treatment considering these findings will help to decrease the mortality.